The Budget Impact of Cangrelor in the UK for the Treatment of Out-of-Hospital Cardiac Arrest Patients Who Require Percutaneous Coronary Intervention - Modi B; Cain R; Stork R; Barwood C; Tarpey G; Colucciello A (ClinicoEconomics and Outcomes Research)
Bhavik Modi,1 Rob Cain,2 Richard Stork,2 Caroline Barwood,3 Gina Tarpey,2 Alessia Colucciello4 1Cardiac Surgery Department, Glenfield Hospital, University Hospitals of Leicester NHS Trust, Leicester, UK; 2Chiesi Ltd, Manchester, UK; 3FIECON Ltd, London, UK; 4Chiesi Farmaceutici S.p.A., Parma, ItalyCorrespondence: Richard Stork, Chiesi Ltd., 333 Styal Road, Manchester, M22 5LG, UK, Email r.stork@chiesi.comBackground: Cangrelor is an intravenous, reversible P2Y12 inhibitor indicated for the reduction of thrombotic cardiovascular events in patients undergoing percutaneous coronary intervention (PCI) who have not received an oral P2Y12 inhibitor prior to the PCI procedure, and in whom oral therapy with P2Y12 inhibitors is not feasible or desirable (for example, in the out-of-hospital cardiac arrest [OHCA] population).Objective: This study aimed to estimate the affordability and budget impact, in the United Kingdom, of introducing cangrelor within the licenced OHCA population.Methods: A budget impact model was developed to estimate the impact of introducing cangrelor to hospitals over 5 years. Efficacy (thrombotic events) and safety (bleeding events) data were based on clinical trials, cost data (2021/22 GBP), literature, NHS reference costs and British National Formulary data. Comparators were glycoprotein IIb/IIIa inhibitors and aspirin in combination with heparin, reflecting current treatments used in UK centres for the target population. Cangrelor uptake was estimated as 50% in Year 1, 75% in Year 2, and 100% in Years 3– 5. The OHCA population was estimated from the British Cardiovascular Intervention Society National Audit 2021/22.Results: Over 5 years, cangrelor leads to modelled cost savings of £ 2,709,853 (− 9.84%), varying from £ 322,218 in Year 1 (− 5.85%) to £ 636,150 (− 11.55%) in Year 5). This is driven by approximately 6,882 hospital days being avoided over 5 years due to fewer bleeding events.Conclusion: Cangrelor for OHCA patients who cannot take oral P2Y12 inhibitors may lead to cost savings in the UK.Keywords: glycoprotein inhibitor, P2Y12 inhibitor, cardiovascular disease, out-of-hospital cardiac arrest, antiplatelet therapy